Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Sepeda Motor Merek Honda Pcx Pada Dealer Tdm Bima - Abal Karima; Muhajirin Muhajirin (Institut Nalanda, 2023)
This research aims to determine the influence of the marketing mix on purchasing decisions for Honda PCX brand motorbikes at TDM Bima dealers. The sample in this study was 52 respondents. Data collection techniques using observation, questionnaires and literature study. Data analysis technique using multiple linear regression. The results of the research show that partially or simultaneously the variables price, product location and promotion have a significant effect on purchasing decisions for Honda PCX brand motorbikes at TDM Bima dealers.